The impact of supply chain finance on firm capital structure adjustment: Evidence from China - Pan, Ailing; Xu, Lei; Li, Bin; Ling, Runze; Zheng, Luyan (Australian journal of management, 2023)
We establish a link between supply chain finance (SCF) and capital structure adjustment by core firms through a data set of listed firms on the Shanghai and Shenzhen Stock Exchanges. We find that SCF can significantly speed up capital structure adjustment, especially for the underleveraged firms. Enhanced financial strengths and competitive advantages underlie this impact. Comprehensive examinations also suggest that SCF may speed up cash turnovers, lower financing costs, and improve firm values. In addition, the impact is more substantial on firms of smaller sizes, located in better-developed regions, those without bank-firm connections, and those with higher environmental dynamism. However, the impact seems similar on private firms and stateowned enterprises (SOEs), or across industries of various degrees of competition. Our findings bear such policy implications that SCF can accelerate capital structure adjustment and contribute to the quality economic growth in emerging markets.